SEMIOTIC STUDY OF SETTLEMENT’S SPATIAL PATTERN IN KUNINGAN REGENCY, WEST JAVA - Kersapati, Muhamad Iko; Setiadi, Hafid (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2021)
This study discusses how people in Kuningan Regency divided into indigenous and immigrant communities interpret human relations with nature as well as changes in the context of the natural environment identified through the configuration of the components of the settlements. The observed natural environments include water, land, forest, and mountains, while the settlement components include houses, village halls, mosques, cemeteries, and rice fields. The data used in this study is qualitative data from various literature, maps, observations, and in-depth interviews. The method used in this study is the method of interpretation to reveal the meaning behind the spatial pattern of settlement as a unity of signs. The results reveal that the influence of water and land was more dominant in nature-depended traditional settlement and transition settlement. Meanwhile, forests and mountains did not have a major impact on the spatial patterns of all three categories of settlements.